Sosialisasi Manajemen Keuangan Rumah Tangga pada Masyarakat Desa Margaasih - Mintarsih, Mimin; Nur'aeni, Nur'aeni; Azis, Abdul (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2025)
The ability to manage household finances is an essential skill that plays an important role in maintaining family welfare and financial stability. Many families, especially in rural areas, still lack adequate understanding of how to plan and manage budgets effectively. This Community Service Program (PKM) aims to improve public understanding of household financial management based on Islamic principles. The method used in this activity was Participatory Action Research (PAR), conducted through socialization, interactive discussions, and evaluation stages. The activity was held on August 2, 2025, in Margaasih Village, Cicalengka District, Bandung Regency, involving community leaders and housewives as participants. The results showed a significant improvement in participants’ understanding of family budgeting, income and expense management, and the application of prudent financial principles aligned with Islamic values. Participants also expressed commitment to implementing daily financial recording and open communication within family financial management. This activity is expected to encourage community financial independence and support the realization of prosperous and empowered families.